2004
DOI: 10.1007/s00705-004-0437-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and spread of Bovine leukaemia virus isolates in Argentine dairy cattle

Abstract: Effective tools for use in control programmes against bovine leukaemia virus (BLV) infections require insight into the relationship between the variant structure of the bovine leukaemia virus and the spatial-temporal interaction of isolates and hosts. Our study showed the presence of two types of BLV isolates - Australian and Argentine - in dairy herds from various parts of Central Argentina; these isolates were characterised by RFLP on PCR amplicons, and some of them were confirmed by sequencing. One genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 29 publications
9
37
2
1
Order By: Relevance
“…Thus, our genotypes 1, 2 and 4 are equivalent to clusters 2, 1 and 3 described by Camargos et al (2007) (Table 1). The sequences AF257515.1, K02120.1 and M35238.1, which clustered into genotypes 2, 1 and 4, were included in the first, third and second clusters described by Monti et al (2005) Table S1). Genotypes 1-6 identified here are indicated with lines surrounding the corresponding tree branches.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our genotypes 1, 2 and 4 are equivalent to clusters 2, 1 and 3 described by Camargos et al (2007) (Table 1). The sequences AF257515.1, K02120.1 and M35238.1, which clustered into genotypes 2, 1 and 4, were included in the first, third and second clusters described by Monti et al (2005) Table S1). Genotypes 1-6 identified here are indicated with lines surrounding the corresponding tree branches.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been shown that the sensitivity and specificity of different serological testing methods already demonstrate significant variation (Trono et al, 2001) and produce different results when compared with molecular methods (Fechner et al, 1996;Reichel et al, 1998). Furthermore, the existence of BLV strains that escape antibody detection, associated with the presence of particular genotypes, has been described (Fechner et al, 1997;Monti et al, 2005). Monti et al (2005) observed that 31 of 445 animals that tested positive by PCR were negative when screened by serological analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En la primera reacción se usaron 25ng de ADN, 10mM de cada cebador "sentido" env 5032 5´-TCTGTGCCAAGTCTCCCAGATA-3´ y "anti sentido" env 5608r 5´-AACAACAACCTCTGGGAA-GGGT-3´, 0.2 mM de cada dNTP, 1X de tampón de PCR, 2.5 mM de MgCl 2 y 1U de Taq DNA Polymerase (Fermentas ® ). En la segunda reacción se utilizó como ADN molde 1µl del producto amplificado de la primera reacción, las mismas concentraciones de los demás reactivos y los cebadores internos "sentido" env 5099 5´-CCCACAAGGGCGGCGCCGGTTT-3› y "anti sentido" env 5521r 5´-GCGAGGCCGGGTCCAGAGCTGG-3´, haciendose ambas reacciones a un volumen final de 15µl (Monti et al, 2005). El perfil térmico de la primera reacción incluyó una desnaturalización inicial a 94°C durante 5 minutos, seguido por 40 ciclos de 94°C por 30 segundos, 60°C por 30 segundos y 72°C por 1 minuto, para terminar con una extensión final a 72°C durante 5 minutos.…”
Section: Presencia Del Vlb Por Métodos Moleculares (Env)unclassified
“…In all sequences deletions and insertions were observed. Insertions and deletions were not observed in BLV pol and env sequences (Coulston et al 1990, Dube et al 1997, Dube et al 2000, Camargos et al 2002, Monti et al 2005. The sequences D00647 and K02120 probably had sequencing errors, as mentioned by others (Dube et al 2000).…”
Section: Resultsmentioning
confidence: 69%